Monitoring an archaeological excavation using photogrammetry and digital elevation models (DEMS): the case study of Barranco León in Orce (Granada, Spain) - González-Quiñones, Juan José; Reinoso-Gordo, Juan Francisco; Solano-García, José Antonio; Cámara-Donoso, José Miguel; León-Robles, Carlos Alberto; Linares-Matás, Gonzalo; Jiménez-Arenas, Juan Manuel (SPAL - Revista de Prehistoria y Arqueología, 2022)
In this paper, we describe and discuss emergent digital technologies employed for monitoring the excavations at the archaeological site of Barranco León (Granada, Spain) between 2017 and 2020. The method entails the following material requirements: a total station, a conventional camera, a computer and a software that integrates photogrammetry algorithms; in terms of human resources, the presence of an engineer for the first day of the excavation to set up the methodological process and trained excavation staff to perform said method on a daily basis is necessary. Here we present the daily workflow for monitoring archaeological excavations introduced at the site, followed by an estimation of the costs and a summary of the results obtained. The method introduced here is based on the height difference of Digital Elevation Models (DEMs) computed on successive days using photogrammetric techniques. It is a non-invasive method, which requires less than 8% of the economic resources of the excavation and can be carried out in less than 15 minutes. This allows the excavation director to have an accurate and visual idea of the excavation process in order to make appropriate decisions. In addition, from the results obtained in the method (differences in DEM of every two days), other derived results can be obtained such as the exact location of the archaeological remains extracted based on their size. These features highlight the relevance and applicability of this approach to a wide range of archaeological sites.